Deep Learning Features Can Improve Radiomics-Based Prostate Cancer Aggressiveness Prediction - Rodrigues, Nuno M. (2024)
Rodrigues, N. M., Almeida, J. G. D., Rodrigues, A., Vanneschi, L., Matos, C., Lisitskaya, M., Uysal, A., Silva, S., & Papanikolaou, N. (2024). Deep Learning Features Can Improve Radiomics-Based Prostate Cancer Aggressiveness Prediction. JCO Clinical Cancer Informatics, 8, Article e2300180. https://doi.org/10.1200/CCI.23.00180 --- Supported in part by FCT, Portugal, through funding of the LASIGE Research Unit (UIDB/00408/2020 [https://doi.org/10.54499/UIDB/00408/2020], UIDP/00408/2020 [https://doi.org/10.54499/UIDP/00408/2020]), and Nuno Rodrigues PhD Grant 10.54499/2021.05322.BD (https://doi.org/10.54499/2021.05322.BD). Ana Rodrigues and José Guilherme de Almeida were supported by the European Union H2020: ProCAncer-I project (EU grant 952159). This work was supported by national funds through FCT (Fundação para a Ciéncia e a Tecnologia), under the project—UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.